Pengaruh jumlah haluan pipa paralel pada kolektor surya plat datar absorber batu kerikil terhadap laju perpindahan panas - M. Wirawan; R. Kurniawan; Mirmanto Mirmanto (Dinamika Teknik Mesin, 2016)
Recently the use of energy increases. It leads to the energy crisis. Therefore, it is important to promote alternative energy (renewable energy). One of renewable energies, which is potential in Indonesia, is solar enrgy. Solar energy can be harvested using a solar collector. This device can collect or absorb solar radiation and convert it to thermal energy. In this study, two identical collectors are used. One collector consists of 7 pipes and the other comprises 9 pipes. The overall dimension of the collector is 100 cm x 80 cm x 10 cm and the absorber of the collector is made of gravels with a mesh size of 9.5 -12.5 mm. The collectors are placed with a slope of 15o facing to North. The volumetric rates of water used in the experiments are 300 cc / min, 350 cc / min and 400 cc / min. The results show that the collector with 9 pipes is better than that with 7 pipes.